Allais, Ellsberg, and preferences for hedging - Mark Dean; Pietro Ortoleva (Theoretical Economics, 2017)
Two of the most well known regularities observed in preferences under risk and uncertainty are ambiguity aversion and the Allais paradox. We study the behavior of an agent who can display both tendencies simultaneously. We introduce a novel notion of preference for hedging that applies to both objective lotteries and uncertain acts. We show that this axiom, together with other standard ones, is equivalent to a representation in which the agent (i) evaluates ambiguity using multiple priors, as in the model of Gilboa and Schmeidler (1989), and (ii) evaluates objective lotteries by distorting probabilities, as in the rank dependent utility model, but using the worst from a set of distortions. We show that a preference for hedging is not sufficient to guarantee Ellsberg-like behavior if the agent violates expected utility for objective lotteries; we provide a novel axiom that characterizes this case, linking the distortions for objective and subjective bets.
Keywords: D81; 330; Ambiguity aversion; Allais paradox; Ellsberg paradox; hedging; multiple priors; subjective mixture; probability weighting; rank dependent utility